Optimizing welding parameters for high deposition efficiency in waam by using the taguchi method - Abdullah, Ahmad Baharuddin; Wani, Zarirah Karrim; Jaafar, Noor Azam (International Journal of Industrial Optimization, 2025)
Wire arc additive manufacturing (WAAM) is a type of additive manufacturing technology that offers high flexibility in shaping products and is cost-effective due to its low material consumption and rapid time to market. Material consumption can be evaluated by assessing deposition efficiency during welding. The efficiency of a deposited metal depends on various processes and welding parameters, including travel speed, wire feed rate, voltage, distance of the torch from the base, and many others. Therefore, process capability can be efficiently achieved by crucially determining the key parameters that have the most significant effect. In this study, the main objective is to determine the most significant parameters to obtain the optimum deposition efficiency of a gas metal arc welding-based 3D welding machine. The Taguchi experimental design method is used to determine the optimal welding parameters. Results showed that the distance of the torch from the base is the most significant parameter, followed by welding speed and wire feed rate. The observation is validated via a confirmation test.